Autoimmune encephalitis: Clinical Features and Long-Term Outcomes - Sara Rute Soares Granja (2022)
Background and objectives: Autoimmune encephalitis (AE) presents with cognitive and psychiatric changes during the acute stage. The extent of dysfunction varies extensively, and it may persist in the long-term. However, few studies have detailed the cognitive and functional outcomes of these patients. We aim to evaluate the functional and cognitive outcomes of patients with AE, as well as to characterize sleep and mood disorders in this population. Methods: We carried a single-centre observational cross-sectional study, including ≥18-yo patients diagnosed with EA with autoantibodies or with definite seronegative limbic encephalitis, at a Portuguese tertiary centre (January 2007-December 2021). Sociodemographic and clinical data was obtained from electronic records. A neuropsychological evaluation, Montreal Cognitive Assessment(MoCA) and questionnaires to assess functional status (Functional Assessment Inventory in Adults and the Elderly[IAFAI]), sleep (Satisfaction, Alertness, Timing, Efficiency and Duration Questionnaire for Sleep Health Measurement [SATED-RU] and Pittsburgh Sleep Quality Index[PSQI-PT]) anxiety and depression (Hospital Anxiety and Depression Scale), were applied in a scheduled appointment. For cognitive scales, impairment was considered when the score was below 1.5sd from normative values. Results: We enrolled thirteen patients (median follow-up 62 months [29-97.5]). Twelve patients(92.3%) were independent according to the modified Rankin Scale, however, IAFAI identified functional impairment in 5 (38.5%). Only 4 patients (30.8%) had an entirely normal neuropsychological evaluation. Five patients (41.7%) showed cognitive impairment on MoCA . Seven patients (58.3%) showed impairment in at least one memory test; the same holds for executive functions. Older age at disease onset correlated with higher functional disability, lower MoCA, and higher verbal memory and executive impairment. Also, higher CSF protein counts correlated with impaired verbal memory and executive functioning tasks. Three subjects presented mild depression (23.1%); anxiety frequency was 38.5%. Five patients (38.5%) reported bad sleep quality, scoring higher in PSQI-PT with greater admission delay (r=0.574, p=0.040). Discussion: Although most times subtle, we found frequent multimodal impairment in this AE population. Older individuals seem more prone to develop disability, suggesting an age-related contribution. Impairment might also be partially attributed to higher inflammation burden in the acute setting. Disability, cognition, mood, and sleep ought to be systematically screened in this setting.